Disaster-Aware Tourist Development Strategy in Puncak Areas Bogor District West Java Province - Drucella Benala Dyahati; Lailan Syaufina; Arzyana Sunkar (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Indonesia is a country located in a disaster-prone region. Disasters in Indonesia have caused adverse impacts on the Indonesian tourism industry. Disaster mitigation efforts are needed to reduce the impact of a disaster. This study aimed to analyze disaster-aware tourist development strategy in Puncak Areas Bogor District West Java Province. The result showed that disaster-aware tourists are tourists who have a good knowledge, attitudes and behavior about disasters. Results of analysis showed that disaster-aware tourists only 25% from total tourists visited Puncak Area. Disaster-aware tourists are tourists who consciously and responsible participate in an efforts of disaster mitigation in order to minimize or overcoming the impact of the disasters especially in tourism industry. Disaster-aware tourists development strategy is imparting disaster-aware tourists behavior on tourists, developing disaster-aware tourists through strengthening the social norm, socialize and promoting disaster-aware tourists concept until adopted into a trend that can support mitigation efforts and increase disaster preparedness, optimizing the role of disaster-aware tourists to encourage supporting infrastructure and mitigation efforts policies in the tourism areas and tourism industry, the government and tourism industry providing disaster-aware tourists supporting infrastructure, increase collaboration between the government, private sector and tourists in order to mend disaster mitigation efforts in the tourism areas and tourism activity, create and implement policies or special rules that regulate disaster mitigation efforts in tourism activity and industry with strength supervison, sanctions, and enforcement.